Cord blood acrylamide levels and birth size, and interactions with genetic variants in acrylamide-metabolising genes - Janneke Hogervorst; Hubert W. Vesper; Narjes Madhloum; Wilfried Gyselaers; Tim Nawrot (BMC, 2021)
Abstract Background Up to now, 3 epidemiological studies have shown clear inverse associations between prenatal acrylamide exposure and birth size. In addition to studying the association between acrylamide and birth size, we investigated the interaction between acrylamide and polymorphisms in acrylamide-metabolising genes, with the aim of probing the causality of the inverse relationship between acrylamide and fetal growth. Methods We investigated the association between prenatal acrylamide exposure (acrylamide and glycidamide hemoglobin adduct levels (AA-Hb and GA-Hb) in cord blood) and birth weight, length and head circumference in 443 newborns of the ENVIRONAGE (ENVIRonmental influence ON AGEing in early life) birth cohort. In addition, we studied interaction with single nucleotide polymorphisms (SNPs) in CYP2E1, EPHX1 and GSTP1, using multiple linear regression analysis. Results Among all neonates, the body weight, length and head circumference of neonates in the highest quartile was − 101 g (95% CI: − 208, 7; p for trend = 0.12), − 0.13 cm (95% CI: − 0.62, 0.36; p for trend = 0.69) and − 0.41 cm (− 0.80, − 0.01; p for trend = 0.06) lower, respectively, compared to neonates in the lowest quartile of AA-Hb in cord blood, For GA-Hb, the corresponding effect estimates were − 222 g (95% CI: − 337, − 108; p for trend = 0.001), − 0.85 (95% CI: − 1.38, − 0.33; p for trend = 0.02) and − 0.55 (95% CI: − 0.98, − 0.11; p for trend = 0.01), respectively. The associations for GA-Hb were similar or stronger in newborns of non-smoking mothers. There was no statistically significant interaction between acrylamide exposure and the studied genetic variations but there was a trend of stronger inverse associations with birth weight and head circumference among newborns with homozygous wildtypes alleles for the CYP2E1 SNPS and with variant alleles for a GSTP1 SNP (rs1138272). Conclusions Prenatal dietary acrylamide exposure, specifically in the form of its metabolite glycidamide, was inversely associated with birth weight, length and head circumference. The interaction pattern with SNPs in CYP2E1, although not statistically significant, is an indication for the causality of this association. Other studies are needed to corroborate this finding.